2015
DOI: 10.1097/meg.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Portuguese version of a questionnaire to measure Quality of Care Through the Eyes of Patients with Inflammatory Bowel Disease (QUOTE-IBD)

Abstract: PT-QUOTE-IBD is acceptable, valid, and reliable in the assessment of Performance and Quality Impact of Total Care, but not of all dimensions of healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…In the QOUTE-IBD, all questions on Importance had a question non-response rate between 1 and 6.5%, although for Performance, the question non-response rate was 27-40%. This is similar to the Portuguese validation study of the QOUTE-IBD, where 92% of the patients answered all questions on Importance, but only 59% completed all the questions in the QOUTE-IBD [33]. In our study, the high response rate in the QoC-Q indicates good acceptability.…”
Section: Variablesupporting
confidence: 87%
“…In the QOUTE-IBD, all questions on Importance had a question non-response rate between 1 and 6.5%, although for Performance, the question non-response rate was 27-40%. This is similar to the Portuguese validation study of the QOUTE-IBD, where 92% of the patients answered all questions on Importance, but only 59% completed all the questions in the QOUTE-IBD [33]. In our study, the high response rate in the QoC-Q indicates good acceptability.…”
Section: Variablesupporting
confidence: 87%
“…This was also seen in the Portuguese validation study of the QOUTE-IBD, where 69% of the patients answered all questions on Performance (89) and 64% of the patients answered all questions on Importance and Performance. This is similar to the Portuguese validation study were only 59% of the patients completed all the questions (89). Study III indicates that there are problems with the QOUTE-IBD in terms of acceptability, due to the low response rate in the performance questions.…”
Section: Drop Out and Question Non Response Study IVsupporting
confidence: 56%
“…In the Portuguese version of the QUOTE-IBD, it was concluded that there is no golden standard for the assessment of quality of care from the perspective of those living with IBD. The need for a shorter and more user-friendly questionnaire was also expressed (89).…”
Section: Assessing Quality Of Carementioning
confidence: 99%
“…9 In dealing with this issue, Sixma et al demonstrated that a more reliable approach was to look at an algorithm of performance, importance and impact scores for the various aspects of healthcare. 1 Sixma's conceptual framework was based on the prior work of Zastowny et al 39 in the Patient Experience Survey (PES) and has influenced the development of instruments, such as the QUOTE [20][21][22][40][41][42][43][44] (Quality Of care Through the patient's Eyes) and CQI (Consumer Quality Index), 19,23,[45][46][47][48][49][50] for assessing patient-reported care quality across various disciplines. Dentistry is yet to develop a validated patient-reporting instrument of its own.…”
Section: 9%mentioning
confidence: 99%